APLICATIAN OF PARTNERSHIP PROGRAM AND ENVIRONMENTAL DEVELOPMENT IN PT. SERVICES RAHARJA PERSERO SOUTH SULAWESI BRANCH - Yuliani, Nur Fadny (Perpustakaan dan Penerbitan Unismuh Makassar, 2018)
The research aim is to know how and the obstacles that occur in the implementation of Partnership and Community Development Program (PKBL) at PT Jasa Raharja South Sulawesi branch. The type of research used is qualitative, which is The researcher described the results of observations and direct interviewed with PKBL sub-part. This research was conducted in March to May 2018. The results showed that the implementation of the Partnership and Community Development Program (PKBL) at PT Jasa Raharja South Sulawesi branch, consist of: 1.General repair help advice, such as portable and hand scoon, 2.Health assistance, such as the provision of masks, hand sanitizers, hand soaps and tools personal health protection, 3.Assistance for religious facilities, such as mosque renovation,4.Social assistance, such as food distribution, 5. Nature conservation, like planting mangroves. While the obstacles were faced n the implementation of Partnership and Community programs are: 1.refundrate loan is still low from partners, 2. Lack of human resources to distribute of assistance.